TI_GERICHTE 12.2009.105 vom 20. Juni 2011 , Appalto - onere di allegazione - onere di contestazione - pena convenzionale - TI Tribunale d'appello (2011)
Appalto - onere di allegazione - onere di contestazione - pena convenzionale